Thermal Properties of Polypropylene/Ionic Liquid Modified Clay Nanocomposites - Wang, L.M. (Asian Journal of Chemistry, 2011)
Polypropylene (PP)/ionic liquild modified clay nanocomposites were successfully synthesized via in situ polymerization based on Ziegler-Natta/clay compound catalyst. Wide angle X-ray diffraction (XRD) analysis proved clay layers were exfoliated into nanometer size in polypropylene matrix and the a-phase was the main crystal phase of polypropylene in the nanocomposites. The presence of clay enhanced the thermal stability of polypropylene materials, since the initial decomposition temperature of polypropylene/clay nanocomposites was evidently bigger than that of pure polypropylene. The crystalliztion temperature of nanocomposites was slightly higher than that of pure polypropylene due to nucleation ability of clay.